Man seeks God : my flirtations with the divine - Weiner, Eric, 1963- (Twelve, 2011)
After a health scare, an atheist travels the world searching for an experience of the divine, from meditating with Tibetan lamas in Nepal and unblocking his chi in China, to studying the Kabbalah in Israel.